High‐Performance Li‐O2 Batteries Enabled by Dibenzo‐24‐Crown‐8 Aldehyde Derivative as Electrolyte Additives. Issue 26 (8th May 2022) - Zhang, Qi; Rao, Sijia; Vummaleti, Sai Vikrama Chaitanya; Poh, Eng Tuan; Dai, Wenrui; Cui, Xinhang; Wu, Jishan; Zhang, Jia; Chen, Wei
Abstract: Aprotic Li‐O2 batteries (LOB) with high theoretical energy density usually experience cathode clogging by insoluble Li2 O2, along with high charge overpotential from its insulating nature. A dibenzo‐24‐crown‐8 aldehyde derivative (DB24C8A) is employed as an additive to enhance the binding strength with Li +, hence promoting the solubility of Li2 O2 . The generated [DB24C8ALi + ] avoids the parasitic reactions caused by reactive O2 − . Thus, the LOB achieves a large discharge capacity of 6939 mAh g −1 at 200 mA g −1 and a high Li2 O2 yield (≈93%). Moreover, DB24C8A facilitates the efficient decomposition of Li2 O2 via Li + coordination during the charge process, reducing the charge overpotential to 0.77 V and prolonging the lifetime of the LOB over 213 cycles at 1000 mAh g −1 and 500 mA g −1 . This work provides a novel approach to boost the performance of LOB by incorporation of crown ether‐based compounds to regulate the Li2 O2 growth and decomposition pathway. Abstract : Dibenzo‐24‐crown‐8 aldehyde derivative (DB24C8A) is employed as an electrolyte additive to achieve 213 cycles, a large discharge capacity of 6939 mAh g −1, a high Li2 O2 yield 93%, and a low charge overpotential 0.77 V for Li‐O2 batteries. The performance is attributed to its strong binding towards Li +, thereby promoting the solution mechanism and facilitating Li2 O2 oxidation. The generated [DB24C8ALi + ] can avoid O2 − induced parasitic reactions.